2022
DOI: 10.1097/lgt.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar High-Grade Squamous Intraepithelial Lesions and Cancer as a Risk Factor for Anal Cancer: A Review

Abstract: Anal squamous cell carcinoma (ASCC) has a higher incidence described in certain groups, namely, in women with vulvar high-grade squamous intraepithelial lesions (vHSILs) and/or human papillomavirus squamous cell carcinoma (VSCC). This review describes terminology, vHSIL, and VSCC in their association with ASCC and the published recommendations for early detection of this cancer in these women. Materials and Methods:A narrative review was conducted by the authors on vHSIL and VSCC as risk factors for ASCC. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
(201 reference statements)
0
6
0
Order By: Relevance
“…Studies have confirmed the elevated prevalence of anal intraepithelial neoplasia in women with HPV-related precancer and cancer [ 12 ]. If an evaluation of the anal canal is needed, the patient should be referred to a clinician with adequate training for this procedure [ 13 ].…”
Section: Diagnostics Of Vulvar Intraepithelial Neoplasiamentioning
confidence: 99%
“…Studies have confirmed the elevated prevalence of anal intraepithelial neoplasia in women with HPV-related precancer and cancer [ 12 ]. If an evaluation of the anal canal is needed, the patient should be referred to a clinician with adequate training for this procedure [ 13 ].…”
Section: Diagnostics Of Vulvar Intraepithelial Neoplasiamentioning
confidence: 99%
“…9,10 Women who have or had high-grade or worse cervical lesions (CIN2/3+) and/ or vulvar high-grade lesions also have a higher risk of anal lesions and cancer. [11][12][13] Moreover, incidence of anal cancer is significantly higher in people living with HIV (PLWH). [14][15][16] The morbidity associated with anal lesion and cancer treatments can be very high.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been linked to an increased risk of anal cancer including age (higher proportion of cases occur in people after 50 years of age), number of sexual partners, history of receptive anal sexual intercourse, smoking and immune capacity 9,10 . Women who have or had high‐grade or worse cervical lesions (CIN2/3+) and/or vulvar high‐grade lesions also have a higher risk of anal lesions and cancer 11‐13 . Moreover, incidence of anal cancer is significantly higher in people living with HIV (PLWH) 14‐16 …”
Section: Introductionmentioning
confidence: 99%
“…The incidence rates of anal SCC in women with vulvar cancer and vulvar HSIL were 48 and 42 per 100,000 person-years, 6 respectively, more than 20 times that described for the general population. Thus, a high index of suspicion for anal SCC should be maintained in these women 7 …”
Section: Epidemiology Of Anal Squamous Cell Carcinomamentioning
confidence: 99%
“…Thus, a high index of suspicion for anal SCC should be maintained in these women. 7 A meta-analysis published after the anal cancer risk scale 6 also analyzed the incidence rate of anal SCC in patients with anal condylomas. 8 The overall incidence rate of anal SCC in these patients was 7 per 100,000 person-years and was higher in men (13 per 100,000 person-years) than in women (5 per 100,000 person-years).…”
mentioning
confidence: 99%